Education and Later-Life Mortality: Evidence from a School Reform in Japan - Kazuya Masuda; Hitoshi Shigeoka (Institute of Labor Economics (IZA), 2023)
We examine the mortality effects of a 1947 school reform in Japan, which extended compulsory schooling from primary to secondary school by as much as 3 years. The abolition of secondary school fees also indicates that those affected by the reform likely came from disadvantaged families who could have benefited the most from schooling. Even in this relatively favorable setting, we fail to find that the reform improved later-life mortality up to the age of 87 years, although it significantly increased years of schooling. This finding suggests limited health returns to schooling at the lower level of educational attainment.
Keywords: H52; I12; I21; I28; 330; education; later-life mortality; secondary school; Japan; regression discontinuity design